De la culture scolaire à la culture du lien - Renaud Hétier (Recherches en Éducation)
At school, the idea of emancipation can lead to a certain type of links to culture, which can be objectifying – and in the meantime, sometimes reifying. Culture becomes a link to cultural objects and by putting such distance, one can fear that children won’t work it out. From an educational point of you, one has to take into account the competition between the media and digital devices with the common school objects - to the disadvantage of the latter. But this competition is uncannily convergent. In some cases of emancipation – of the knowledge and leisure consumer – whom one can’t understand how it can become really emancipatory, it is the same reification process that prevails. Thus, the above competition is uncannily converging. One has to be careful on the reconsideration of the link in the construction, the transmission and sharing process. The link to the object, the link to others via this object, the link to the object via others may be necessary if one takes into account the emotional reality of the human experience and the goal of a work on culture. This work is allowed by being available to others and the interdependence – which are also the results of this work – can be thought as an alternative to an emancipation by knowledge.